Effect of gaiters on muscle pump activity in healthy volunteers. (September 2013) - IWata, H; Hirai, M; Miyazaki, K; Koyama, A; Ikeda, K; Hukiage, M; Kitamura, H
Objectives: Exercise of the leg with external limb compression has been reported to be useful for preventing and reducing leg oedema. The aim of this study was to investigate the effects of leg gaiters on calf muscle pump activity. Methods: Continuous measurements of the interface pressure at the leg during exercise and determination of the femoral venous velocity at the groin during exercise were carried out in healthy volunteers with elastic stockings alone, leg gaiters alone and gaiters over the elastic stockings. Results: The greatest pressure difference between muscle contraction and relaxation during exercise was observed when gaiters were applied over the elastic stockings at the calf. Gaiters alone without elastic stockings led to a significantly greater pressure difference between muscle contraction and relaxation during exercise than elastic stockings alone (P, 0.01). A significantly higher value of the peak flow velocity of the femoral vein was observed with the combined use of gaiters and elastic stockings than the single use of elastic stockings. Conclusions: Leg gaiters have a beneficial effect of augmenting venous femoral blood flow during calf muscle pump activity in volunteers with a normal valve function of leg veins.